The National Surgical, Obstetric, and Anesthesia Plan (NSOAP): Recognition and Definition of an Empirically Evolving Global Surgery Systems Science; Comment on "Global Surgery - Informing National Strategies for Scaling Up Surgery in Sub-Saharan Africa" - Gregory L. Peck; Joseph S. Hanna (Kerman University of Medical Sciences, 2018)
In 2015, the Lancet Commission on Global Surgery (LCoGS) working groups developed a National Surgical, Obstetric, and Anesthesia Plan (NSOAP) framework to guide national surgical system development globally predicated on six data points (indicators) which can assess surgical systems. Zambia as well as other subSaharan Africa (SSA) countries have forged ahead in designing and implementing interventions based on LCoGS indicators collected to inform NSOAP. Concurrently, the Zambian team and others have recognized the need for rigorous scientific inquiry to assess and iteratively improve upon the NSOAP process and outputs. Based on the Zambian experience, as well as that of ours in Colombia, we have identified "core principles" through convergent works which inform a scientific framework through which NSOAP can be evaluated. We propose that when contextualized, participatory action research (PAR) and dissemination and implementation science are methodologies upon which a robust framework can be developed to achieving objective and iterative NSOAP evaluation, and ultimately universal health coverage as envisioned by the World Health Organization (WHO).